The UK, the European Union and NATO: Brexit's unintended consequences. Issue 5 (19th October 2016) - Dunn, David Hastings; Webber, Mark
Abstract : The result of the UK referendum on membership of the EU has occasioned considerable debate on Britain's international standing. An important (but so far largely overlooked) aspect of this debate is how the possibility of Brexit impacts upon NATO and, specifically, the UK's position within the Atlantic alliance. In this connection, the initial signs are worrying. London may wish to focus on NATO as a way of compensating for a troubled exit from the EU, but its ability to do so is weakened by uncertainties over the UK defence budget (and standing as a nuclear power), a loss of credibility as a global player and the blame that will attach to it for undermining NATO cohesion. The likely upshot of Brexit will be a loss of British influence and a blow to the integrity of the alliance.